Accuracy of Expressing Greetings, Farewells and Forms of Address in English by Taxy Drivers in Nusa Dua Resorts, Bali - Muliana, I Wayan; Pastini, Ni Wayan; Lilasari, Luh Nyoman Tri (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2024)
This study examines the accuracy with which taxi drivers at Nusa Dua International Resort in Bali express interrelated language functions, specifically greetings, farewells, and forms of address. Data were collected from 50 respondents through a test consisting of 14 situational questions in Bahasa Indonesia, yielding a total of 1,100 responses. The results indicate that 518 responses (47%) were correct, while 582 (53%) were incorrect. Among the 18 expected expressions, the three most common errors were found in